Micropropagation of Brasilidium forbesii (Orchidaceae) through transverse and longitudinal thin cell layer culture - Lucas Roberto Pereira Gomes; Cristina do Rosário Batista Franceschi; Luciana Lopes Fortes Ribas (Acta Scientiarum. Biological Sciences, 2015)
An efficient in vitro propagation method was established for Brasilidium forbesii (Hook.) Campacci using transverse and longitudinal thin cell layer (tTCL and lTCL, respectively) culture systems. Six-month-old protocorms from in vitro germinated seeds were used for this study. TCLs (1.0-mm thick) from protocorms were grown on Woody Plant Medium (WPM) supplemented with benzyladenine (BA) (0.5–4.0 µM).The lTCL technique was more efficient for inducing protocorm-like bodies (PLBs) and regenerating shoots than the tTCL technique. The frequency of PLB formation was influenced by BA concentration, and the lTCL explant grown on a medium containing 2.0 µM BA produced the highest percentage of new protocorms (77%) with a total of 22.7 PLBs per explant, after the first subculture on the same medium. Plantlet development was optimal on WPM medium containing 3.0 g L-1 activated charcoal, and indole-3-butyric acid was not necessary for rooting. Regenerated plants were successfully acclimatized in a greenhouse after 16 weeks using vermiculite as the substrate (100% survival).